2017
DOI: 10.4184/asj.2017.11.5.832
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-Invasive versus Conventional Repair of Spondylolysis in Athletes: A Review of Outcomes and Return to Play

Abstract: Spondylolysis from pars fracture is a common injury among young athletes, which can limit activity and cause chronic back pain. While current literature has examined the relative benefits of surgical and conservative management of these injuries, no study has yet compared outcomes between conventional direct repair of pars defects and modern minimally invasive procedures. The goals of surgery are pain resolution, return to play at previous levels of activity, and a shorter course of recovery. In this review, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
16
0
3
Order By: Relevance
“…In a retrospective study of 16 patients with spondylolysis undergoing direct pars repair with the Buck’s screw technique, Snyder et al [ 61 ] demonstrated that Buck’s screw repair provided a satisfactory clinical and radiological outcome, including an early RTS. In a review of minimally invasive versus conventional direct repair of pars for spondylolysis in athletes, Kolcun et al [ 62 ] reported that patients undergoing minimally invasive pars repair had significantly higher rates of pain resolution and shorter recovery times. Both groups were comparable in terms of complication rates and RTP rates.…”
Section: Spondylolysis and Spondylolisthesismentioning
confidence: 99%
“…In a retrospective study of 16 patients with spondylolysis undergoing direct pars repair with the Buck’s screw technique, Snyder et al [ 61 ] demonstrated that Buck’s screw repair provided a satisfactory clinical and radiological outcome, including an early RTS. In a review of minimally invasive versus conventional direct repair of pars for spondylolysis in athletes, Kolcun et al [ 62 ] reported that patients undergoing minimally invasive pars repair had significantly higher rates of pain resolution and shorter recovery times. Both groups were comparable in terms of complication rates and RTP rates.…”
Section: Spondylolysis and Spondylolisthesismentioning
confidence: 99%
“…Descriptions of the individual techniques and the available outcome data are well summarized in the 2011 review article by Drazin et al, in which they conclude that any of the described techniques for repair will likely yield acceptable results in young athletes [4]. Modern minimally invasive techniques for direct spondylolysis repair may have superior clinical outcomes over conventional open techniques and may be considered in cases where conservative management has failed [29].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Современные исследователи, изучая спондилолиз, традиционно придерживаются двух основных теорий его происхождения и развития: врожденной [9,16,17] и приобретенной [18][19][20][21][22]. Основоположником теории о врожденном происхождении принято считать Ф.л.…”
Section: материал и методыunclassified
“…учитывая тот факт, что основным клиническим симптомом спондилолиза являются боли, в литературе активно обсуждается лечебная тактика в отношении пациентов, страдающих этой патологией [21,55,70,71]. Значительная часть исследователей придерживается консервативного метода в купировании болевого синдрома, используя в качестве лечебных средств исключение нагрузок на поясничный отдел позвоночника, физиотерапию, корсетирование, массаж, лекарственные средства и мануальную терапию [45,46,52,65,72,73].…”
Section: материал и методыunclassified
See 1 more Smart Citation